Needs assessment for introducing pulmonary rehabilitation for chronic obstructive pulmonary disease management in a rural Indian setting: a qualitative study - Hilary Pinnock; Sudipto Roy; Sanjay Juvekar; Dhiraj Agarwal; Diksha Naresh Singh; Harshpreet Kaur (BMJ Open Respiratory Research, 2023)
Background Pulmonary rehabilitation (PR) is an effective strategy to improve breathlessness, health status and exercise tolerance and to reduce readmissions and mortality. In India, there is no government health programme for chronic obstructive pulmonary disease (COPD) management while in the private sector availability of PR is limited. Most PR centres are in urban areas, with few services accessible to rural populations. We aimed to assess the need for PR from the perspective of patients with COPD and healthcare professionals (HCPs: registered medical practitioners and medical officers) in rural Maharashtra.Methodology Between June and October 2020, we conducted semi-structured interviews with 14 patients with COPD and 9 HCPs to explore their perceptions of, and need for, PR in rural Maharashtra. Interviews were transcribed and analysed thematically.Results We approached 14 patients with COPD and 9 HCPs practising in rural areas. Five HCPs stated that they did not advise PR for patients with COPD citing poor compliance to PR referral and follow-up of the patients. Patients with COPD had symptoms and needs that could be helped by PR but commented how transportation would be a problem for them to visit a PR centre. In contrast, they could understand the benefits of PR and expressed their willingness to join such programmes. A PR service was established that addressed these needs.Conclusion Patients with COPD have unmet needs that could benefit from attending a PR programme, but there are barriers at both healthcare and patient levels that we addressed in a new PR service for people with chronic respiratory disease in rural Maharashtra.